Safety climate in the Malaysian furniture industry - Ooi, Chung Hun (2012)
The wood-based industry has long been an important segment of Malaysia’s dynamic manufacturing sector, which is the main driver of economic growth for the country. The industry has also played a significant role as an export earner. The Malaysian furniture industry is an important component of the country’s wood-based manufacturing sector. According to the Social Security of Malaysia (SOCSO), the total registered local workforce was 11 million people in 2010, while the wood-based industry employs 380,000 people. Therefore, in order to prevent and reduce the number of industrial accidents and occupational diseases among the work force, the Malaysian government has enforced two most important legislations: the Occupational Safety and Health Act (OSHA) of 1994 and the Factories and Machinery Act (FMA) of 1967. At the same time, the Employees’ Social Security Act of 1969 is used to deal with accidents and diseases which are not successfully avoided. Although, the government has been effort to reduce the industrial accidents, but the results are not significant. Actually, the key to the prevention of occupational accidents, and work-related diseases and the promotion of workers’ health and well-being at work must include: (i) promotion and awareness raising and advocacy; (ii) legal instruments, laws, regulations and their national enforcement, that is labour inspection; (iii) knowledge development; management and dissemination; (iv) technical assistance and cooperation and (v) international collaboration. This study defines the structure of the safety climate as perceived by the workers and correlations between the safety climate and safety practice of the company, the safety level of the working environment with particular emphasis on dust, safety in wood machining operations, noise level and waste disposal in the Malaysian furniture industry, using a structure questionnaire and data from the SOCSO. The study found that there were four factors that represents the results, which are: 1) company responsibility; 2) workers’ safety attitudes; 3) safety supervision; and 4) company safety precautions. The result shows that the safety climate factor of company responsibility and factor of company safety precautions had a significant correlation with the accident rate and the safety level in the work environment. This proves that, the company responsibility which consisted by top management and safety precautions have a strong influence on the safety climate among the workers in the work place. However, even though the actual rate of accidents in the working place was low and decreased over the past few years, but the compensation rate paid by the SOCSO, clearly showed an image that the safety climate with a small amount of local worker is unstable, with indirect losses due to occupational accidents being uncountable. The research has revealed that, the best way to increase level of safety climate among the wood products industry should be implemented through a systematic management and operational approach, such as ISO 14000 Standard registration and occupational health and safety management system, to ensure a safe working environment can be created and maintained at anytime in the Malaysian furniture industry.